Understanding the impact of 5-HTTLPR, antidepressants, and acute tryptophan depletion on brain activation during facial emotion processing: a review of the imaging literature - Raab, Kyeon; Kirsch, Peter; Mier, Daniela (Neuroscience & biobehavioral reviews, 2016)
Detecting and evaluating emotional information from facial expressions as a basis for behavioural adaption belong to the core social-cognitive abilities of mankind. Dysfunctions in emotional face processing are observed in several major psychiatric disorders like depression and schizophrenia. In search for psychiatric disease biomarkers using the imaging genetics approach, serotonergic gene polymorphisms have been associated with altered brain circuit activation during emotional face processing. Especially the 5-HTTLPR gene polymorphism has been extensively investigated in association with emotion regulation processes. In this article, imaging genetics literature on emotional face processing, reporting genetic effects of 5-HTTLPR in healthy volunteers is reviewed. Additionally, these results are regarded in relation to pharmacologic challenge (antidepressants, acute tryptophan depletion) imaging studies and discussed in light of recent neurobiological evidence with a focus on serotonin (5-HT1A, 5-HT2C, 5-HT2A) receptor findings.
Gesehen am 10.04.2019
Available online 1 September 2016